Sites of Cellular Autolysis in Lactobacillus acidophilus - Higgins, M. L. (1973)
Ultrastructural changes which occur during cellular autolysis of Lactobacillus acidophilus strain 63AM Gasser in 0.05 M citrate buffer, pH 5.0, were examined. Early in the process, randomly distributed electron-dense patches were seen on the wall surface, along with an accompanying eversion of mesosomes. Later, after a loss of about 20% of the initial cellular turbidity, dissolution from the outside of nascent cross walls was seen. This observation was related to the normal process of cell separation. After this stage, short lengths of the cylindrical portion of the wall appeared to be completely removed in a random manner over the entire surface. This dissolution produced gaps in the wall which allowed the extrusion of membrane and cytoplasm. Although membrane was usually extruded through one major, polar, subpolar, or septal site, other secondary points of membrane extrusion were also frequently seen in the same cell section.